ANTIOXIDANT ACTIVITY OF PLANT PARTS EXTRACTS FROM STERCULIA QUADRIFIDA R. BR. - GRACE SEREPINA SARAGIH; SISWADI SISWADI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Sterculia quadrifida R. Br. of Sterculiaceae family is locally known as “Faloak” in East Nusa Tenggara Province, Indonesia. S. quadrifida is used in folk medicine to treat hepatitis, rheumatism, and to recover stamina. The aim of this study was to determine the total flavonoids, total phenolic content (TPC), and antioxidant activity of extracts from different plant parts of S. quadrifida. Methods: The sampled parts of S. quadrifida were non-stripped stem bark, new regrown stem bark, old regrown stem bark, root bark, branch bark, and leaves. Stem bark was classified into three categories, namely, bark that has never been peeled (non-stripped stem bark), old regrown stem bark (estimated to be >6 months after debarking), and new regrown stem bark (estimated to be <6 months after debarking). Total flavonoid content (TFC) was determined by colorimetric aluminum chloride method and TPC was measured using Folin–Ciocalteu’s reagent. Antioxidant activity was determined with 2,2-diphenyl-1-picrylhydrazyl (DPPH). Results: The concentrations of flavonoids in S. quadrifida extracts from different plant parts varied from 0.58±0.13 to 1.25±0.10 mg QE/g. The TPC in the extracts of different plant parts ranged between 8.61±0.09 and 10.43±0.08 mg GAE/g. Branch bark has the highest total flavonoid and phenolic content. The extract of new regrown stem bark exhibited potent antioxidant activity with inhibitory concentration (IC50) values of 2.51±0.03 μg/ml. Conclusion: This study demonstrated for the first time that extracts from different plant parts of S. quadrifida exhibited strong antioxidant activity. However, the total phenolic and flavonoid contents in S. quadrifida only indicated a weak correlation with its antioxidant activity.